A Deferential Krsna: The Unstolen Cows of Harivamsa 113 - Austin, Christopher R. (Religions of South Asia, 2022)
This paper examines the concluding scene (chapter 113) of the Harivamsa’s Krsna biography, in which Krsna tries to steal some cows, but then chooses not to. I argue that the episode should be understood first in connection with the Mahabharata’s amsavatarana frame of partial incarnations. Secondly, I bring to bear on Harivamsa 113 the multiple meanings of the cow in epic mythology, according to which the animal stands in for both the earth and the brahmin as paradigmatic objects of ksatriya protection. In so doing, I hope to provide a reading of Harivamsa 113 which illustrates its participation in a recurring epic theme of ksatriya transgression against the brahmin and subsequent retreat to a properly deferential position. I then historicize these bovine-encoded anxieties attending brahmin-ksatriya relations in their post-Mauryan context. Recognizing such themes at work in Harivamsa 113 can help us to see that, however much popular traditions may favour the playful and transgressive Krsna, his posture in the latter part of the Harivamsa is characterized by a complex conservatism informed by both historic and epic-mythological concerns.